2014
DOI: 10.5901/ajis.2014.v3n1p189
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Corrupt Practices of Academics: What Conditions Promote Them?

Abstract: The study delved into corrupt practices perceived to be pervasive in academic institutions especially that of academics. The exercise was motivated by the paucity of information on where the alleged practice emanates from and the conditions in academic institutions perceived to be promoting the practice. The cross-sectional survey utilised students from two universities in Ghana. Questionnaire was the main research instrument used for the data gathering. The instrument was validated through peer review and pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…Non-commencement of semester examination as scheduled, non-release of semester results, lack of supervision of SIWES exercise, allowing students to see examination questions before time, forcing students to buy handouts, errors in the computation of GPA and CGPA, non-release of degree results on time, and delay in mobilization of graduates for the NYSC programmes are some of the examination-related challenges encountered by technology education in other degree awarding institutions in north-eastern Nigeria. This finding is in contrast with the views of Kuranchie et al (2014) who opined that most tertiary institutions have zero tolerance to all illicit behaviours such as selling of grades and other unwholesome behaviours; however, the findings aligned with the views of Ajayi and Adeniji (2009) who argued that tertiary institutions in Nigeria are becoming a shadow of what they used to be, because in the current dispensation, students are at liberty to earn grades of their choices when they are ready to engage in some sort of unwholesome behaviours such as buying their way either in "cash" or in "kind". It also reinforced the findings of Ogbonnaya (n.d) who discovered that lack of adequate supervision of SIWES programme enable most of students to developed truant behaviour when posted for the exercise.…”
Section: Discussioncontrasting
confidence: 94%
“…Non-commencement of semester examination as scheduled, non-release of semester results, lack of supervision of SIWES exercise, allowing students to see examination questions before time, forcing students to buy handouts, errors in the computation of GPA and CGPA, non-release of degree results on time, and delay in mobilization of graduates for the NYSC programmes are some of the examination-related challenges encountered by technology education in other degree awarding institutions in north-eastern Nigeria. This finding is in contrast with the views of Kuranchie et al (2014) who opined that most tertiary institutions have zero tolerance to all illicit behaviours such as selling of grades and other unwholesome behaviours; however, the findings aligned with the views of Ajayi and Adeniji (2009) who argued that tertiary institutions in Nigeria are becoming a shadow of what they used to be, because in the current dispensation, students are at liberty to earn grades of their choices when they are ready to engage in some sort of unwholesome behaviours such as buying their way either in "cash" or in "kind". It also reinforced the findings of Ogbonnaya (n.d) who discovered that lack of adequate supervision of SIWES programme enable most of students to developed truant behaviour when posted for the exercise.…”
Section: Discussioncontrasting
confidence: 94%
“…The study findings on the positivity of the students' perception of assessment irregularities of their lecturers are in agreement with the study of [10] which disclosed that students' perception of corrupt practices of academics in Ghana was positive. That study identified favouritism, nepotism, and examination malpractices as the forms of irregularities perceived by the students.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…In a study on the perceived corrupt practices of academics in Ghana [10] disclosed that "favouritism, nepotism and examination malpractices were perceived by students as being the main elements of corruption among university teachers". Other factors revealed by the survey as promoting the act were fear of victimization, fear of school authority and bureaucracy in dealing with such issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The level of corruption among the students of higher institutions is capable of making the institutions fail to produce capable and transparent people needed to enhance development. Kuranche, Twene, Mensah and Arthur [2014] asserted that the moral upbringing of students of tertiary educational institutions is paramount to the sustainability and development of the societies they are being trained for.…”
Section: Introductionmentioning
confidence: 99%